Oxygen tension differentially regulates the functional properties of cartilaginous tissues engineered from infrapatellar fat pad derived MSCs and articular chondrocytes. - Kelly, Daniel; Buckley, Conor (My University, 2010)
Background For current tissue engineering or regenerative medicine strategies, chondrocyte (CC)- or mesenchymal stem cell (MSC)-seeded constructs are typically cultured in normoxic conditions (20% oxygen). However, within the knee joint capsule a lower oxygen tension exists. Objective The objective of this study was to investigate how CCs and infrapatellar fad pad derived MSCs will respond to a low oxygen (5%) environment in 3D agarose culture. Our hypothesis was that culture in a low oxygen environment (5%) will enhance the functional properties of cartilaginous tissues engineered using both cell sources. Experimental design Cell-encapsulated agarose hydrogel constructs (seeded with CCs or infrapatellar fat pad (IFP) derived MSCs) were prepared and cultured in a chemically defined serum-free medium in the presence (CCs and MSCs) or absence (CCs only) of transforming growth factor-beta3 (TGF-?3) in normoxic (20%) or low oxygen (5%) conditions for 42 days. Constructs were assessed at days 0, 21 and 42 in terms of mechanical properties, biochemical content and histologically. Results Low oxygen tension (5%) was observed to promote extracellular matrix (ECM) production by CCs cultured in the absence of TGF-?3, but was inhibitory in the presence of TGF-?3. In contrast, a low oxygen tension enhanced chondrogenesis of IFP constructs in the presence of TGF-?3, leading to superior mechanical functionality compared to CCs cultured in identical conditions. Conclusions Extrapolating the results of this study to the in vivo setting, it would appear that joint fat pad derived MSCs may possess a superior potential to generate a functional repair tissue in low oxygen tensions. However, in the context of in vitro cartilage tissue engineering, CCs maintained in normoxic conditions in the presence of TGF-?3 generate the most mechanically functional tissue.
PUBLISHED
PMID: 20650328
Keywords: Bioengineering; Cartilage repair; Agarose hydrogel; Infrapatellar fat pad; MSCs; Chondrocytes; Functional properties; Oxygen tension; Next Generation Medical Devices